(untitled) (Research, Society and Development, 2022)
Objective: To discuss the contributions and impacts of extension by professors, stricto sensu graduate students and high school students at the Federal Institute of Mato Grosso do Sul (IFMS), with the theme of the use of household cleaning products and the possible environmental impacts, in Campo Grande, Mato Grosso do Sul, during the social isolation of the covid-19 pandemic. Method: Descriptive study with a qualitative approach in stages: (I) survey of students’ prior knowledge; (II) synchronous and asynchronous lectures and dialogues; (III) research of products sold in the city; (IV) selection of insecticides and photographic records of the labels; (V) identification of active ingredients; (VI) substances that make up the products; (VII) production of a scientific glossary of substances; (IX) correct disposal of household cleaning products; (X) lecture on the subject; (XI) elaboration and dissemination of a folder for a cultural exhibition during the IFMS Environment Week. Conclusion: The theoretical contributions built and developed through the extension project on insecticide products for domestic use have become important teaching and learning strategies in the current period with the inappropriate use of these products; emphasizing, above all, the potential damage to human health and the environment. In this sense, essential skills were developed for the future professional practice of students and graduate students, such as communication, teamwork, technological mastery in the construction of the technical bulletin.